Orientasi Ideologi dan Pragmatisme Politik Model Pembentukan Koalisi dalam Pilkada Serentak di Jawa Tengah 2015 - Luthﬁ Makhasin (Jurnal Ilmu Sosial dan Ilmu Politik, 2016)
This article explains the making of intra party coalition prior to and during simultaneous local direct election phase I in Central Java Province, held in 9 December 2015. Referring to and modifying from the current scholarly works on the coalition making and politico-ideological orientation of political party in Indonesia, it oﬀers four typologies of intra party coalition which are small ideological coalition, small pragmatic coalition, grand ideological coalition, and grand pragmatic coalition. The case of coalition making in the local direct election in 21 districts/municipalities in Central Java Province reveals that political party is a powerful and irreplaceable political player in democratic setting. As a formal political institution, it is and will remain considerably inﬂuential in nominating and endorsing candidates to run in the local direct election.